2015
DOI: 10.1152/jn.00149.2015
|View full text |Cite
|
Sign up to set email alerts
|

Prediction strength modulates responses in human area CA1 to sequence violations

Abstract: Emerging human, animal, and computational evidence suggest that, within the hippocampus, stored memories are compared with current sensory input to compute novelty, i.e., detecting when inputs deviate from expectations. Hippocampal subfield CA1 is thought to detect mismatches between past and present, and detected novelty is thought to modulate encoding processes, providing a mechanism for gating the entry of information into memory. Using high-resolution functional MRI, we examined human hippocampal subfield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 47 publications
7
67
1
Order By: Relevance
“…A separate fMRI study showed that the hippocampal CA1 subregion is sensitive to temporal context information, such that hippocampal representations of the same target item differed depending on whether it was preceded by its two original images or two slightly similar images (Wang & Diana, ). This finding accords with other work showing that different hippocampal sub‐regions respond to temporal sequence (Chen, Cook, & Wagner, ; Kim et al, 2017) and temporal order violations (Azab, Stark, & Stark, ), as well as expected stimulus violations more broadly (Duncan, Ketz, Inati, & Davachi, ). Furthermore, the hippocampus has also been shown to be sensitive not only to item violations but also temporal duration violations; however, in this instance, hippocampal activity was greater when the expected item appeared (Barnett et al, ).…”
Section: Proactive Mechanisms Of Binding Sequential Memory Representasupporting
confidence: 92%
“…A separate fMRI study showed that the hippocampal CA1 subregion is sensitive to temporal context information, such that hippocampal representations of the same target item differed depending on whether it was preceded by its two original images or two slightly similar images (Wang & Diana, ). This finding accords with other work showing that different hippocampal sub‐regions respond to temporal sequence (Chen, Cook, & Wagner, ; Kim et al, 2017) and temporal order violations (Azab, Stark, & Stark, ), as well as expected stimulus violations more broadly (Duncan, Ketz, Inati, & Davachi, ). Furthermore, the hippocampus has also been shown to be sensitive not only to item violations but also temporal duration violations; however, in this instance, hippocampal activity was greater when the expected item appeared (Barnett et al, ).…”
Section: Proactive Mechanisms Of Binding Sequential Memory Representasupporting
confidence: 92%
“…Finally, hippocampal responses to unexpected outcomes were associated with subsequent behavioral expressions of memory updating, with greater hippocampal out- come responses predicting relatively faster retrieval of new associations and relatively slower retrieval of older associations. Compared with prior reports of hippocampal mismatch signals Maguire, 2006a, 2006b;Duncan et al, 2009Duncan et al, , 2012Chen et al, 2015), a critical-and novel-advantage of our experimental approach is that we measured directly, on a trialby-trial basis, neural prediction strength. Although the hippocampus is known to act as a novelty detector (Stern et al, 1996;Strange et al, 1999;Ranganath and Rainer, 2003), the mismatch signal is not thought to simply reflect associative novelty, but to reflect a comparison between an actively generated prediction and a new, but unexpected associative outcome (Kumaran and Maguire, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the hippocampus may play a critical role both in generating predictions and comparing predictions to outcomes (Hasselmo and Wyble, 1997;Lisman and Grace, 2005;Kumaran and Maguire, 2007;Chen et al, 2015). That said, when we decoded prediction strength directly from the hippocampus, it was not related to univariate hippocampal outcome responses.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations